2014
DOI: 10.1097/fjc.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

Signaling via P2Y12 May Be Critical for Early Stabilization of Platelet Aggregates

Abstract: P2Y(12) receptor antagonism inhibits platelet aggregation by preventing adenosine diphosphate (ADP)-mediated amplification of activation pathways downstream of primary agonists, such as thrombin and collagen. However, the role of ADP signaling in maintaining aggregate stability and the effects of P2Y(12) antagonists on preestablished aggregates in vitro and arterial thrombus in vivo are not well understood. This study evaluated the impact of P2Y(12) signaling on platelet aggregate stability and early thromboti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…There are some limited data that reversible P2Y 12 inhibitors may not be effective at dispersing established arterial thrombi and thus cangrelor may have a lower risk of re-bleeding in stenting performed in patients with ruptured aneurysms. 18…”
Section: Discussionmentioning
confidence: 99%
“…There are some limited data that reversible P2Y 12 inhibitors may not be effective at dispersing established arterial thrombi and thus cangrelor may have a lower risk of re-bleeding in stenting performed in patients with ruptured aneurysms. 18…”
Section: Discussionmentioning
confidence: 99%
“…e presence of coronary thrombus at the time of angiography is known to worsen outcomes following ACS [14]. Furthermore, in vitro models have shown that P2Y 12 agents can disrupt and even reverse thrombus stability [15,16]. Longer pretreatment with P2Y12 agents is also associated with improved coronary perfusion before PCI [17].…”
Section: Benefits Of Early Versus Delayed Angiographymentioning
confidence: 99%
“…A phase I study in humans showed that Revacept dose-dependently inhibited collagen-induced platelet aggregation without a significant effect on bleeding time. In contrast, ADP- or thrombin receptor activating peptide-dependent platelet aggregation remained unaltered [ 66 ].…”
Section: Novel Antithrombotic Drugs That May Impact On Thrombus Stabimentioning
confidence: 99%